QUALITY PARAMETERS OF REFRIGERATED RAW MILK PRODUCED IN THE NORTHERN REGION OF ESPÍRITO SANTO, BRAZIL - Passinato, Arthur Oliveira; Piccolo, Maria da Penha; Donatele, Dirlei Molinari; Araujo, Arthur Loss; Massini, Lívia Silveira; Figueredo, Iago Cesar de Souza; Oliveira, Maysa do Vale; Batista, Julianne Soares Jardim Lacerda (Seven Editora, 2025)
The objective of this study was to evaluate the quality parameters of raw milk samples stored in individual refrigeration tanks on three family farms in the northern region of Espírito Santo. Microbiological quality was assessed by analyzing the total bacterial count (TBC) and psychrotrophic bacteria count (PBC). Proximate composition was also determined using a Lactoscan® device, and somatic cell count (SCC) was measured using a Somaticell® kit. Some characteristics of the farms, the location of the tanks, and the temperature used during storage were assessed. Total bacterial count values ​​were within the legally established limit, and the psychrotrophic bacteria count was below the 10% suggested TBC. The average somatic cell count obtained in samples collected from tank A was 650,000 SC/mL, from tank B it was 500,000 SC/mL, and from tank C it was 250,000 SC/mL. Regarding the centesimal composition, it was observed that the milk samples obtained from tanks A and B presented percentages of fat, solids-non-fat, and total solids below the legally recommended values, while the milk samples from tank C presented rates above or close to the established minimum values. In contrast, the percentages of protein and lactose approached the recommended minimum limits. The data showed that the temperature values ​​recorded in the three refrigeration tanks were in accordance with the legislation. Regarding psychrotrophic bacteria, the values ​​were below those suggested in the literature, but it is necessary to reinforce care and surveillance regarding somatic cells, which are indicative of mastitis in the herd. Continued frequent evaluation of the parameters analyzed in other samples will be of great importance, as it will contribute to monitoring possible failures in production and processing and will enable the supply of adequate milk and dairy products, in addition to the sustainability of the sector in the northern region of the state of Espírito Santo, Brazil.DOI: https://doi.org/10.56238/sevened2025.039-001